Persistence of long COVID symptoms in COVID-19 survivors worldwide and its potential pathogenesis - A systematic review and meta-analysis - Fahriani, Marhami; Ilmawan, Muhammad; Fajar, Jonny K.; Maliga, Helnida A.; Frediansyah, Andri; Masyeni, Sri; Yusuf, Hanifah; Nainu, Firzan; Rosiello, Francesco; Sirinam, Salin; Keam, Synat; Ophinni, Youdiil (Narra Sains Indonesia, 2021)
The study sought to determine the prevalence of persistent long COVID symptoms such as anxiety, depression, dizziness, chest pain, sleep difficulty, palpitations, weight loss, and hair loss among coronavirus disease 2019 (COVID-19) survivors worldwide and to discuss the potential pathogeneses. Potential studies were searched in three databases (PubMed, Scopus, and Web of Science) as of January 30, 2021. Data on study characteristics, patient characteristics during the follow-up, the number of patients with persistent long COVID symptoms and total COVID-19 survivors were collected according to PRISMA guidelines. To assess the quality of studies, the Newcastle-Ottawa scale was used. The estimated prevalence of each long COVID symptom and the association between COVID-19 severity and the occurrence of prolonged symptoms was assessed, if appropriate. The global prevalence of prolonged anxiety was 15.76% (95%CI: 6.36%, 25.15%). Chest pain persisted in 10.36% (239/3,224) of COVID-19 patients (95%CI: 4.92%, 15.80%). Prolonged depression was found in 24 of 548 COVID-19 survivors with an estimated prevalence of 4.32% (95%CI: 2.62%, 6.03%) and dizziness was presented in 4.83% (118/2,219, 95%CI: 1.50%, 8.16%) after recovery. Hair loss was complained by 527 of 2,251 recovered patients (cumulative prevalence of 24.76%, 95%CI: 19.60%, 29.91%), while weight loss was identified in 37 cases among 452 COVID-19 survivors (8.19%, 95%CI: 5.66%, 10.71%). Prolonged palpitation was experienced by 19.38% (211/1,926) survivors with 95%CI: 2.40%, 41.16%. Sleep difficulty was found in 541 of 2,622 COVID-19 survivors (17.87%, 95%CI: 7.55%, 28.20%). The association between COVID-19 severity and the occurrence of persistent long COVID symptoms was not analyzed due to the lack of data. In conclusion, persistent psychological symptoms are frequently reported among COVID-19 survivors. Follow-up studies with a longer duration and larger population are warranted to assess the extent of prolonged symptoms and the quality of life of COVID-19 survivors. Despite various potential pathogeneses that have been hypothesized, a definitive mechanism is yet to be addressed.